A systematic review and critical analysis of the role of graphene-based nanomaterialsin cancer theranostics - Viseu, Teresa (2020)
: Many graphene-based materials (GBNs) applied to therapy and diagnostics (theranostics) in cancer have been developed. Most of them are hybrid combinations of graphene with other components (e.g., drugs or other bioactives, polymers, and nanoparticles) aiming toward a synergic theranostic effect. However, the role of graphene in each of these hybrids is sometimes not clear enough and the synergic graphene effect is not proven. The objective of this review is to elaborate on the role of GBNs in the studies evaluated and to compare the nanoformulations in terms of some of their characteristics, such as therapeutic outcomes and toxicity, which are essential features for their potential use as bionanosystems. A systematic review was carried out using the following databases: PubMed, Scopus, and ISI Web of Science (2013–2018). Additional studies were identified manually by consulting the references list of relevant reviews. Only English papers presenting at least one strategy for cancer therapy and one strategy for cancer diagnostics, and that clearly show the role of graphene in theranostics, were included. Data extraction and quality assessment was made by reviewer pairings. Fifty-five studies met the inclusion criteria, but they were too heterogeneous to combine in statistical meta-analysis. Critical analysis and discussion of the selected papers are presented.